2021
DOI: 10.1177/1120672121995347
|View full text |Cite
|
Sign up to set email alerts
|

Paracentral acute middle maculopathy in the setting of central retinal artery occlusion following COVID-19 diagnosis

Abstract: Background: Since its emergence in Wuhan, China, COVID-19 has disseminated across many other countries worldwide. In this report, we firstly presented a patient with mild COVID-19 disease who developed paracentral acute middle maculopathy (PAMM) due to CRAO. Case presentation: A 54-year-old male patient who reported a contact with a COVID-19 patient applied to the hospital and tested positive for SARS-CoV-2 by polimerase chain reaction testing. He had no significant past medical history. Chest computed tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 10 publications
1
25
1
1
Order By: Relevance
“…Alessandro et al [ 13 ] reported a case of central retinal vein occlusion 2 days after the COVID-19 diagnosis. Neslihan et al [ 14 ] reported a case of central retinal artery occlusion (CRAO) and paracentral acute middle maculopathy 2 weeks after COVID-19 diagnosis. Andrea et al [ 15 ] reported a case of Central retinal vein occlusion after hospitalization for COVID-19 pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Alessandro et al [ 13 ] reported a case of central retinal vein occlusion 2 days after the COVID-19 diagnosis. Neslihan et al [ 14 ] reported a case of central retinal artery occlusion (CRAO) and paracentral acute middle maculopathy 2 weeks after COVID-19 diagnosis. Andrea et al [ 15 ] reported a case of Central retinal vein occlusion after hospitalization for COVID-19 pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Various authors have described retinal vascular occlusions, including CRAO, BRVOs, and CRVOs in association with COVID-19 ( Table 2 ). 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 The present report is the first and largest case series of CRVO and HRVO occurring after COVID-19. It nearly doubles the currently published cases in the literature and is the only one to exclude predisposing risk factors.…”
Section: Discussionmentioning
confidence: 63%
“…Reported ocular manifestations in the literature to date include conjunctivitis, 10 retinal microangiopathy, 11 , 12 , 13 , 14 , 15 , 16 , 17 paracentral acute middle maculopathy, acute macular neuroretinopathy, 18 uveitis, 19 , 20 and optic neuropathy. 19 , 20 , 21 Additionally, multiple reports describing retinal vascular events such as central retinal artery occlusions, 22 , 23 , 24 , 25 branch retinal vein occlusions (BRVO), 26 , 27 hemiretinal vein occlusion (HRVO) and central retinal vein occlusion (CRVO), 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 and papillophlebitis, 37 following a diagnosis of COVID-19 have been published. The series presented herein expands on the literature and aims to highlight a potential temporal association between COVID-19 infection and the development of retinal vein occlusions (RVO) in otherwise young, healthy patients without other risk factors for RVO.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 infection causes vascular occlusion by causing endothelial damage or increasing systemic thrombotic factors [3] . Retinal artery occlusion, PAMM and acute macular neuro-retinopathy cases associated with COVID-19 have also been reported in the literature [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%